2018
DOI: 10.1089/jmf.2017.4068
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 Inhibition by Genistein: Biological Evaluation, Kinetic Analysis, and Molecular Docking Simulation

Abstract: β-site amyloid precursor protein cleaving enzyme 1 (BACE1) plays a role in generating amyloid β (Aβ), thus playing a major part early in the pathogenesis of Alzheimer's disease (AD). BACE1 has emerged as a crucial therapeutic target for decreasing the Aβ concentration in the AD brain. To explore natural BACE1 inhibitors, the present study concentrated on isoflavones, including genistein, formononetin, glycitein, daidzein, and puerarin. In this study, in vitro anti-AD activities were assessed using BACE1 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
1
23
1
4
Order By: Relevance
“…BBR has also been found to inhibit the expression of cyclin D1 and p53, keeping cells in the G0/G1 phase to prevent neuronal apoptosis [113]. The antioxidant action of BBR has been demonstrated [106,109,114] and its mechanism has also been studied. Glutathione (GSH) is an important antioxidant and Glutathione peroxidase (GPx) is a free-radical scavenger.…”
Section: Berberinementioning
confidence: 99%
“…BBR has also been found to inhibit the expression of cyclin D1 and p53, keeping cells in the G0/G1 phase to prevent neuronal apoptosis [113]. The antioxidant action of BBR has been demonstrated [106,109,114] and its mechanism has also been studied. Glutathione (GSH) is an important antioxidant and Glutathione peroxidase (GPx) is a free-radical scavenger.…”
Section: Berberinementioning
confidence: 99%
“…According to our present study, sulforaphane, as a non-competitive BACE1 inhibitor, had high selectivity for BACE1 as compared to the other aspartyl and serine proteases, indicating that the compound was a safe natural inhibitor of side effects. Many natural BACE1 inhibitors showed non-competitive modes, such as green tea catechins, stilbenoids, coumarins, citrus flavonoids, and ellagitannin [ 21 , 22 , 23 , 24 ]. A previous study by Fang et al (2017) demonstrated that non-competitive BACE1 inhibitors from natural sources deserved further study because of their non-competitive inhibition modes and different structures from those active site directed inhibitors, which may support a new approach to overcoming problems faced with competitive inhibition [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…amyloid precursor protein) poprzez sekretazy (β-sekretazy i γ-sekretazy) [63]. Kluczowym enzymem odpowiedzialnym za ten proces jest β-sekretaza 1 (BACE1) [64]. Youn i wsp.…”
Section: Możliwości Użycia Genisteiny W Leczeniu Choroby Alzheimeraunclassified
“…Silne wiązanie powstaje w miejscu allosterycznym BACE1. Hamowanie proteazy związane jest z budową strukturalną, konkretnie z obecnością grupy hydroksylowej C-5 w pierścieniu A. Wykazano, że w wyniku działania genisteiny na enzym BACE1 dochodzi do zahamowania patologicznych procesów indukowanych poprzez βA, a co za tym idzie -zahamowania apoptozy (badania przeprowadzone zarówno na liniach komórek SHSY5Y jak i na modelach zwierzęcych) [64].…”
Section: Możliwości Użycia Genisteiny W Leczeniu Choroby Alzheimeraunclassified
See 1 more Smart Citation